Pengembangan Konten Digital Sebagai Upaya Peningkatan Literasi Masyarakat Jember Tentang Covid-19 - Maidah, Nova El; Maududie, Achmad; Amalia, Karina Nine (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2021)
The development of digital content on the CovidCare page is carried out as an effort to increase public awareness of Jember about Covid-19. Through the content on the CovidCare page, apart from making it easier for people to register as vaccination participants, it also makes it easier for health facilities to provide vaccination services. Digital content development is carried out through the stages of needs assessment, design, development, and implementation, as well as evaluation and revision.